The Process of Deterioration of Liberal Democracy in the Visegrad Group Countries: Institutional Perspective - Kubas, Sebastian (Politologija, 2022)
Contemporary changes of liberal democracy affect different countries of the world. The Czech Republic, Hungary, Poland and Slovakia, known as the Visegrad Group countries (V4), are among them. Although the countries seemed to be on a good way to consolidated democracy, about a decade ago the first symptoms of deterioration of liberal democracy became apparent. In the text, attention is focused on the institutional level, which should resist certain challenges in mature democracies. The institutions in V4 were weak and liable to be subordinated by strong political leaders and populist parties, and not strong enough to fight off illiberal tendencies. The analysis reveals that Poland and Hungary were more prone to compromise liberal democratic achievements, while the Czech Republic and Slovakia less so. This paper answers the questions of the institutional causes behind the deterioration of liberal democracy and the effects it brings.
Keywords: democratization; liberal democracy; Visegrad Gourp Countries